2002
DOI: 10.1046/j.1471-5740.2002.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Water temperature as a factor in handwashing efficacy

Abstract: For many years, sanitarians have specified that the hands of food service workers should be washed and rinsed in warm or hot water to reduce the risk of cross‐contamination and disease transmission. In the food service environment, it has been suggested that handwashing with water at higher temperatures contributes to skin damage when frequent handwashing is necessitated, and that insistence on hot water usage is a deterrent to handwashing compliance. Separate handwashing studies involving different water temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Two separate studies, Michaels et al (26) and Courtenay et al (11), used inoculated ground beef as debris and found log reductions of an inoculated surrogate similar to those in our study. Michaels et al (26) reported a 1.5-to 2.5-log CFU reduction of Serratia marcescens, with a 15-s wash using antimicrobial soap; Courtenay et al (11) observed a 2.7-log reduction.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Two separate studies, Michaels et al (26) and Courtenay et al (11), used inoculated ground beef as debris and found log reductions of an inoculated surrogate similar to those in our study. Michaels et al (26) reported a 1.5-to 2.5-log CFU reduction of Serratia marcescens, with a 15-s wash using antimicrobial soap; Courtenay et al (11) observed a 2.7-log reduction.…”
Section: Discussionsupporting
confidence: 85%
“…The FDA Model Food Code recommends washing hands for 20 s, under warm running water, with soap, and using either single-use towels or a forced air dryer to dry hands. Although the factors that influence hand washing effectiveness have been studied, these studies may not be comparable due to methodological differences (10) or statistical flaws (11,17,26). Evidence of the efficacy of air drying versus paper towel drying is contradictory.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2004), food service facilities (Paulson et al . 1999; Paulson 2000; Taylor 2000; Lane 2001; Michaels 2002; Michaels et al . 2002; Kerr et al .…”
Section: Introductionmentioning
confidence: 99%
“…82 Water temperature has little effect on the removal of microorganisms from hands, but warm (as opposed to cold) water improves compliance. 88 Moisturizing soaps and lotions can preserve skin integrity and encourage adherence to hand hygiene protocols among veterinary staff. Dry, cracked skin is painful, indicates compromised skin integrity, and is more likely to be colonized with staphylococci and gram-negative organisms.…”
Section: Veterinary Standard Precautionsmentioning
confidence: 99%